Hidradenitis Suppurativa: Current Understanding of Pathogenic Mechanisms and Suggestion for Treatment Algorithm - Seyed Jafari, S. Morteza; Hunger, Robert E.; Schlapbach, Christoph (Frontiers in Medicine, 2020)
Hidradenitis suppurativa is one of the most distressing dermatological conditions and has a significant negative impact on patients ' quality of life. However, the exact pathogenic mechanisms remain incompletely understood and - therefore - efficient therapies are still lacking. The current manuscript focuses on new findings on its pathogenic mechanisms and aims to provide practical therapy recommendations.